2021
DOI: 10.1210/clinem/dgab372
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Predictors of 30-day Readmission Following Diabetic Ketoacidosis in Type 1 Diabetes Mellitus: A US Analysis

Abstract: Introduction This study aimed to describe rates and characteristics of non-elective 30-day readmission among adult patients with diabetes mellitus type 1 (T1DM) hospitalized for diabetic ketoacidosis (DKA) and also identify predictors of readmission. Methods The study analyzed the 2018 Nationwide Readmission Database. DKA hospitalizations in patients with T1DM were classified using ICD-10-CM codes. We utilized Chi-square test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…[11] While predictors and causes for readmission among patients hospitalized for DKA are multifactorial and require further study, previous studies have shown this population to be at high readmission risk and have elucidated some of these risk factors including preexisting medical comorbidities, age, malnutrition, and leaving against medical advice. [11,12] Thus, investigation on multidisciplinary interventions to mitigate risk and prevent readmissions in DKA patients is needed. Additional limitations include potential downstream crossover in levels of care that may be unaccounted for; a considerable proportion of SRO patients (31.8%) with mild-to-moderate DKA managed in the ICU for reasons not addressed; and patients admitted to Med Surg at SRF without an established nonICU continuous insulin infusion protocol in place.…”
Section: Discussionmentioning
confidence: 99%
“…[11] While predictors and causes for readmission among patients hospitalized for DKA are multifactorial and require further study, previous studies have shown this population to be at high readmission risk and have elucidated some of these risk factors including preexisting medical comorbidities, age, malnutrition, and leaving against medical advice. [11,12] Thus, investigation on multidisciplinary interventions to mitigate risk and prevent readmissions in DKA patients is needed. Additional limitations include potential downstream crossover in levels of care that may be unaccounted for; a considerable proportion of SRO patients (31.8%) with mild-to-moderate DKA managed in the ICU for reasons not addressed; and patients admitted to Med Surg at SRF without an established nonICU continuous insulin infusion protocol in place.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies further these findings by analyzing the rate of readmission for diabetic ketoacidosis in type 1 diabetes. Multiple concomitant complications, hypertension, female sex, and incompliance towards medical advice were significant predictors of readmission (32).…”
Section: Discussionmentioning
confidence: 94%
“…A model based on CCSR categories present in the DPG file was mapped from disease groups in the Sundararajan's adaptation of the modified Deyo's CCI [15]. We included smoking history, obesity, malnutrition, and anemia as variables that have impacted mortality in prior HCUP studies [20][21][22]. Mortality is a common outcome of administrative database analysis, which has demonstrated high reliability in coding [23].…”
Section: Outcome Measuresmentioning
confidence: 99%